Light for the artist - Jacobs, Ted Seth. (Mineola, New York : Dover Publications, Inc., 2014)
"Intermediate and advanced art students receive a broad vocabulary of effects with this in-depth study of light. Topics include basics, use of light to define form and space, field effects, colored light, and many other subjects. Diagrams and paintings illustrate applications of principles to figure, still life, and landscape paintings"--
Includes index.
Keywords: Art -- Technique; Visual perception; Light in art; Light; ART / Techniques / Oil Painting